Elements of offering : principles, practices and pointers for Anglican liturgy - John-Julian ([Nashotah, Wis.] : Nashotah House Press, 2014)
There was a time in the 1940s and 1950s when, for Anglo-Catholics at least, there was clearly "One Right Way" to celebrate the liturgical rites of the Church. It was found in the American Missal or the Anglican Missal and was usually called "The Western Rite"--More or less a close Anglican adaptation of Roman Catholic practice of the time. In the 1960s and 1970s, however, that approach and the eventual effects of the Second Vatican Council (astoundingly and unexpectedly convened by Blessed John XXIII) meant that the Roman Rite became much less rigidly defined and a very significant liturgical change took place in the Roman Catholic Church in America. The Episcopal Church during the same years was working its way towards a similarly radical liturgical development with the 1979 Book of Common Prayer. These changes meant that Anglo-Catholics were faced with the need to re-assess their liturgical practices. For some, that meant a rigid adherence to the already outdated Roman Rite of the 1950s. For others it meant reversing the process and rejecting much (or even most) of the past practices and making up brand new liturgy by the yard. It can be accurately said that in the 1980s and 1990s there was no longer "One Right Way". Written with an eye to seminarians and priest, the contents of this book describe a number of principles on which liturgical decisions have been made, a number of practical processes for those who are responsible for liturgy. -- Introduction, p.i-ii.
Keywords: Episcopal Church -- Book of Common Prayer -- Handbooks, manuals, etc; Episcopal Church -- Liturgy; Episcopal Church